Depoliticizing compliance - Ulfstein, Geir (Promoting Compliance in an Evolving Climate Regime, 2011)
IntroductionInternational climate cooperation is first and foremost of a political character. It is essential that political leaders commit to reductions in greenhouse emissions, adaptation measures, protection of forests, and transfer of financial resources and capacity building. At the same time, the need for independent organs and experts is also acknowledged. The scientific authority of the Intergovernmental Panel on Climate Change (IPCC) is based on its independence and expertise and the secretariat of the United Nations Framework Convention on Climate Change (FCCC), while accountable to the Conference of the Parties/Conference of the Parties Serving as the meeting of the parties to the Kyoto Protocol (COP/CMP), is independent from individual state parties, and is expected to respect professional standards. This independence from political interference is seen as a guarantee of a reliable execution of the task at hand.Likewise, both effectiveness and legitimacy may be served by establishing independent organs with power to control national implementation of international climate change obligations. First, depoliticization may be achieved through establishment of independent organs (‘institutional independence’). Second, depoliticization may take the form of legalization, i.e. through establishing commitments and procedures in binding legal instruments (‘formal independence’). Depoliticization, while important, must be controlled. Due process guarantees (‘procedural safeguards’) are a quid pro quo in the sense that empowered independent organs should be subject to procedural control. Moreover, independent organs should be politically accountable. In this way the circle is completed: independent organs are established by political organs and are accountable to such organs.